2007
DOI: 10.2176/nmc.47.95
|View full text |Cite
|
Sign up to set email alerts
|

Case Volume Does Not Correlate With Outcome After Cerebral Aneurysm Clipping: A Nationwide Study in Japan

Abstract: The present study analyzed the impact of case volume on outcome after cerebral aneurysm clipping at all 382 core neurosurgical training centers certified by the Japan Neurosurgical Society. A survey requested information on all clipping surgeries for cerebral aneurysms performed during 2003. Among these centers, 369 (96.6%) responded to our request and data satisfactory for analysis were obtained for 11,974 patients. Clinical condition was graded on admission according to the classification of the World Federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
1
36
2
Order By: Relevance
“…The lower mortality in high-volume hospitals may therefore have been confounded, for instance, by differences in length of stay and discharge routines. [1][2][3][4]7,8,[12][13][14]16,18 Furthermore, all previous studies except 2 originated in the US and the analyses include data from hospitals where multidisciplinary neurosurgical care is likely to be less available or absent. [1][2][3][4]7,8,13,14,16,18 Results from these studies may not be generalizable to health care systems in other countries where specialist neurosurgical services are centralized to tertiary regional hospitals with a defined population and patients are referred from smaller hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower mortality in high-volume hospitals may therefore have been confounded, for instance, by differences in length of stay and discharge routines. [1][2][3][4]7,8,[12][13][14]16,18 Furthermore, all previous studies except 2 originated in the US and the analyses include data from hospitals where multidisciplinary neurosurgical care is likely to be less available or absent. [1][2][3][4]7,8,13,14,16,18 Results from these studies may not be generalizable to health care systems in other countries where specialist neurosurgical services are centralized to tertiary regional hospitals with a defined population and patients are referred from smaller hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 One study from Japan found no relationship between hospital volume and functional outcome (Glasgow Outcome Scale score) at discharge after treatment of ruptured and unruptured intracranial aneurysms. 12 One study from the United Kingdom examined the relationship between hospital volume and 6-month mortality after (aneurysmal and nonaneurysmal) SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes at discharge and six months post-surgery were assessed by using the modified Rankin's Scale (mRS score 0-6, Table 2). A dichotomised mRS score, based on other aneurysm studies (3,6,7), was used as a clinical outcome measurement for patients post clipping. The mRS scores of 0 to 2 were grouped into the "favourable" and mRS scores of 3 to 6 were grouped into the "unfavourable" categories.…”
Section: Methodsmentioning
confidence: 99%
“…Survey of the outcomes of aneurysm surgery in Japan found the surgical mortality of 4,396 UIAs was 0.2%. 7) The case volume of the institution did not affect the surgical outcome in this survey. Quality of life (QOL) score was also analyzed in several outcome studies.…”
Section: Management Outcome and Risksmentioning
confidence: 63%